2017
DOI: 10.3892/etm.2017.4315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and epilepsy outcomes following surgery caused by focal cortical dysplasia (type IIa) in 110 adult epileptic patients

Abstract: The aim of the present study was to investigate the effects of surgical intervention of focal cortical dysplasia (FCD) IIa on the outcome of epilepsy, and to evaluate the prognostic factors of seizure freedom. Patient data from epilepsy surgeries were retrospectively reviewed at the Second Affiliated Hospital of Dalian Medical University between 2007 and 2015. A total of 110 patients with a definite pathological diagnosis of FCD IIa were included. Moreover, the clinical characteristics, seizure outcome and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(51 reference statements)
3
8
0
1
Order By: Relevance
“…The observation that the extent (i.e., completeness) of resection had a significant influence on post-surgical outcome is in concordance with previous publications ( 10 , 12 , 21 , 35 37 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The observation that the extent (i.e., completeness) of resection had a significant influence on post-surgical outcome is in concordance with previous publications ( 10 , 12 , 21 , 35 37 ).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, since some of these patients could not be reached any more (changing address, etc. ), and some of them did not provide a written informed consent for the phone interview, we cannot completely rule out that the slight worsening tendency—though reported in several studies ( 35 )—partially resulted from a disequilibrium of patients as described above.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the current study, patients with a medical record had a less favorable Engel classification, similar to Mariani V et al [15]. Conversely, Sun et al [16] describe that 33.6 % have a positive history, most of them in the Engel I class.…”
Section: Discussionsupporting
confidence: 81%
“…Several authors, in turn, identified this factor as a predictor of good prognosis in extratemporal surgery. [4,5,16,21,[25][26][27][28][29] The use of intraoperative electrocorticography in our environment has become increasingly important to delimit the resection edges and is related to the best results of the present research. Studies with ECoG offer more excellent coverage of areas of the cortex surface and allow spatial contiguity in detecting the ictal onset and its immediate propagation, the complete resection guided by ECoG of the cortical area that presents a FCD pattern, is a predictor of an excellent postsurgical prognosis detected by Morales et al [6] in Cuba and other authors.…”
Section: Discussionmentioning
confidence: 96%